Pelatihan Coding Dasar untuk Siswa Sekolah Menengah sebagai Upaya Penguatan Kompetensi Digital - Fathurrohman; Fatihanursari Dikananda; Alimun Hakim; Anita Ayu Hardani (AMMA : Jurnal Pengabdian Masyarakat, 2022)
This Community Partnership Program aims to provide basic coding training to high school students to enhance their competence in the digital era. The training is designed to introduce programming concepts, computational logic, and problem-solving skills through an easy-to-understand programming language. Activities include an introduction to algorithms, simple data structures, and the development of small coding projects. It is expected that through this training, students can develop computational thinking skills, increase creativity, and prepare themselves to face technological challenges in the future.